Hydrolysis of transferrin promoted by a cerium(IV)-Keggin polyoxometalate. (15th September 2019) - Moons, Jens; Van Rompuy, Laura S.; Rodriguez, Alvaro; Abdelhameed, Shorok A.M.; Simons, Wouter; Parac-Vogt, Tatjana N.
Graphical abstract: Selective hydrolysis of Transferrin (Tf), a glycoprotein consisting of 679 amino acids and three glycan chains has been achieved in the presence of Ce(IV)-substituted Keggin polyoxometalate [Ce IV (α-PW11 O39 )2 ] 10− under physiological conditions (pH = 7.4 and at 37 °C), demonstrating the potential of polyoxometalates to act as artificial proteases. Abstract: Hydrolysis of Transferin (Tf), a glycoprotein consisting of 679 amino acids and three glycan chains, has been examined in the presence of Ce(IV)-substituted Keggin polyoxometalate [Ce IV (α-PW11 O39 )2 ] 10− (Ce-K POM). Incubation at pH = 7.4 and at 37 °C resulted in selective fragmentation of the Tf after 24 h, which was followed by sodium dodecyl sulphate–polyacrylamide gel electrophoresis (SDS–PAGE). After 5 days of incubation nearly 90% of Tf was hydrolyzed, giving 9 fragments with molecular weight (Mw) in the range between 13.7 and 69.5 kDa. Under the same conditions, the sample of Tf which did not contain the Ce-K POM, showed only 7% of background hydrolysis. The interactions between Ce-K and Tf were studied by tryptophan fluorescence, circular dichroism (CD) and 31 P Nuclear magnetic resonance (NMR) spectroscopy. The association constant ( K a ) for the interaction was calculated to be 3.2 × 10 4 M −1 from tryptophan quenching studies. CD spectroscopy revealed that binding of Ce-K to Tf resulted in significant secondary structure changes, mainly affecting the alpha-helical content of the protein. 31 P NMR spectroscopy showed that in the presence of the Tf partial reduction of Ce(IV) to Ce(III) occurred, which did not affect the overall structure of the Keggin POM.